MODERN EDUCATIONAL TECHNOLOGIES FOR TEACHING A FOREIGN LANGUAGE - Tamara Kavilova; Bahrom Karaboshev; Ikrom Karaboshev (Journals Park Publishing, 2022)
The active introduction of educational projects into the educational process can be called relatively innovative, since project activities have always determined the main directions in the development of the learning process. We dwelled on the most general issues of the development of learning theory, showing its evolution as a whole system. The modern innovative development of domestic didactics is based on a solid, historically verified foundation of pedagogical theory and practice. The application of the system-activity approach in modern conditions of education leads to a new way of analyzing pedagogical phenomena. Multidimensionality does not mean differences in the characteristics of the essence of the phenomenon, but comprehensiveness - in the analysis of the whole. Therefore, new cognitive perspectives are opening up for modern researchers of the learning process.
Keywords: modern didactics; educational techniques; intensive teaching methods